PREPARATION OF MYCOPLASMA SYNOVIAE ANTIGENS AND EVALUATION BY RAPID SLIDE AGGLUTINATION AND ENZYME LINKED IMMUNOSORBENT ASSAY - A. Rasool; A. A. Anjum; M. Rabbani; M. Lateef; M. Nawaz; F. Akhtar; A. Kanwal; S. Sattar (Journal of Animal and Plant Sciences, 2017)
Poultry industry has high annual growth rate in Pakistan. Mycoplasmosis, separately or in combination with other diseases, cause major setbacks to poultry industry. Due to significant role of Mycoplasmosis in poultry industry, its control programme success depends on timely and accurate diagnosis of infected flocks. Poultry flocks are generally screened for Mycoplasma by Rapid Slide Agglutination (RSA) test and Enzyme Linked Immunosorbent Assay. Aim of the current project was to prepare and evaluate indigenous Mycoplasma synoviae RSA antigen and ELISA plate coating antigen. M. Synoviae isolates were characterized using 16s rRNA polymerase chain reaction. RSA antigen was prepared using Rose Bengal dye and compared with a commercially prepared RSA antigen. Incubation of ELISA plate, coated with indigenous antigen, at 4oC and 37oC had no significant difference (P=1.0000), but there was a significant difference (P value = 0.01) in the ELISA antibody titers of plates, coated with local antigen incubated at 37oC compared with pre coated plates available in imported kit. ELISA plate coating antigen and RSA antigen of M. synoviae prepared from local isolate is cheap and produced equally reliable results to their commercial companion.
Keywords: Mycoplasma synoviae; Rapid Slide Agglutination; Rose Bengal dye; Local isolate; ELISA